A newborn with a large mass: vacuum extraction‐caused dura lesion. Issue 1 (6th December 2015) - Poryo, Martin; Yilmaz, Umut; Linsler, Stefan; Gortner, Ludwig; Meyer, Sascha
Key Clinical Message: We report on a newborn with a large, high parieto‐frontally located mass after vacuum extraction. Imaging methods revealed a large subcutaneous collection of cerebrospinal fluid and hemorrhage. Traumatic dura lesions should be considered in neonates presenting with a large head lump after assisted delivery with vacuum extraction. Abstract : We report on a newborn with a large, high parieto‐frontally located mass after vacuum extraction. Imaging methods revealed a large subcutaneous collection of cerebrospinal fluid and hemorrhage. Traumatic dura lesions should be considered in neonates presenting with a large head lump after assisted delivery with vacuum extraction.